Development of the Warm Astrometric Mask for MICADO Astrometry Calibration. (12th April 2019) - Rodeghiero, G.; Sawczuck, M.; Pott, J.-U.; Glück, M.; Biancalani, E.; Häberle, M.; Riechert, H.; Pernechele, C.; Naranjo, V.; Moreno-Ventas, J.; Bizenberger, P.; Perera, S.; et al.
Abstract: The achievement of microarcsecond relative astrometry in the near-infrared, with ground-based extremely large telescopes (ELTs) requires an extremely careful calibration strategy. In this paper we address the removal of optical distortions originating from the ELT's first light instrument MICADO and its adaptive optics system MAORY by means of a Warm Astrometric calibration Mask (WAM). The results of the test campaign on small spatial scales (1.5 mm) of a prototype mask has confirmed the manufacturing precision down to ∼50 nm/1 mm scale, leading to a relative precision of δσ ∼ 5 · 10 −5 . The assessed manufacturing precision indicates that an astrometric relative precision of δ σ ∼ 5 · 10 − 5 = 50 μ as 1 ″, corresponding to the MICADO astrometric requirement, is in principle achievable, reaching microarcsecond near-infrared astrometry on an ELT. The impact of ∼20 nm, (peak to valley) error residuals on position of the pinholes of the mask is tolerable at a calibration level as confirmed by ray tracing simulations of realistic MICADO distortion patterns affected by mid spatial frequencies (MSFs) residuals. Here we demonstrate that the MICADO astrometric precision of 50 μ as over 1″ field of view is also achievable in the presence of a MSFs pattern and manufacturing errors of the WAM, found by fitting the distorted WAM pattern seen through the instrument with a 10th order Legendre polynomial.